Vitamin E, glutathione S-transferase and γ-glutamyl transpeptidase activities in cultured hepatocytes of rats treated with carcinogens - Ong, F.B.; Wan Ngah, W.Z.; Top, A.G.M.; Khaud, B.A.K.; Shamaan, N.A. (Elsevier, 1994)
1. 1. The effects of α-tocopherol and γ-tocotrienol on glutathione S-transferase (GST) and γ-glutamyl transpeptidase (γ-GT) activities in cultured hepatocytes prepared from rats treated with diethylnitrosamine (DEN) and 2-acetylaminofluorene (AAF) were investigated. 2. 2. Both the α-tocopherol and γ-tocotrienol treated hepatocytes showed significantly higher (P < 0.05) GST activities than untreated hepatocytes prepared from the carcinogen treated rats in the first 3 days of culture. Treatment with α-tocopherol and γ-tocotrienol generally resulted in a tendency to increase the GST activities above that in the untreated hepatocytes. 3. 3. Treatment with high doses (125-250 μM) of α-tocopherol and low doses (12.5-25 μM) of γ-tocotrienol generally resulted in a significant reduction in γ-GT activities at 1-3 days. γ-GT activities are reduced as the dose of α-tocopherol and γ-tocotrienol are increased.